ANALYSIS OF FLOOD HAZARDS IN MAGETAN REGENCY USINGDISTANCE SENSING METHOD - Jamilah, Zahrotin; Widodo, Amien; Singgih Purwanto, Moh (Journal of Marine-Earth Science and Technology, 2021)
Flood is an annual disaster that hits all over Indonesia, and Magetan Regency is one of the affected area . The high regional topography in the western part and the relatively flat topography in the eastern part making it potential for flood to be higher in the eastern part. The DEM (Digital Elevation Model) topography, Landsat maps, and hazard index maps can be identified by remote sensing using regional administration map data, the level of slope slope and vegetation density can be mapped using NDVI method, and the classification of the flood risk level of an area can be done using ArcGIS software. The slope of the slope and the density of vegetation will affect the level of potential flood hazard. There is a low level of potential for flooding on steep slopes because the air will flow and accumulate on the lower plains. Higher vegetation density will provide a good air catchment area. The level of vegetation density is also higher in the western part. Based on the percentage of the affected area, the low flood hazard level reaches 73.3%, so it can be concluded that the flood hazard level in Magetan Regency is low. It is necessary to provide adequate land and channels capable of providing air flow.